Discriminant Validity: A Comparison of CBSEM and Consistent PLS using Fornell & Larcker and HTMT Approaches - Wan Mohamad Asyraf, Wan Afthanorhan; Nik Mohd Norfadzilah, Nik Mohd Rashid; Puspa Liza, Ghazali (2021)
Discriminant validity is recognized as the essential approach in structural equation modelling method to determine the construct uniqueness in a research model. Using this approach, the applied researchers can identify the distinction role on each construct applied in the study. To date, there are several available approaches has been introduced to perform the discriminant validity. In applied research, the Fornell & Larcker approach is known as the method of choice for discriminant validity. Thus, this study attempt to make a comparison Fornell & Larcker approach with HTMT using CBSEM and Consistent PLS. From here, the results revealed that HTMT based Consistent PLS approach is comparable to Fornell & Larcker based CBSEM but not empirical standard to Fornell & Larcker based Consistent PLS. The discussion and recommendations also provided for this justifications.